PERAN PERBANKAN SYARIAH DALAM MENINGKATKAN KESEJAHTERAAN PETANI SAWIT DI DESA GENTING JUAR KEC. SEMIDANG ALAS MARAS KAB. SELUMA - Zetriana, Yeti; Andang Sunarto; Nurrahmah Putry (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2024)
The purpose of this research is to investigate how sharia banking has affected oil palm producers in Genting Juar Village, Kec. Semidang Alas Maras District. Seluma. Researchers used 11 in-depth interviews and qualitative research methods to collect primary data. It was concluded from the research that sharia banks help oil palm producers by providing them with operating capital, which, if used wisely, may increase their income.